2022
DOI: 10.3390/genes13020298
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-10 Promotes Progesterone Synthesis in Bovine Ovarian Granulosa Cells via Downregulation of microRNA-1246

Abstract: The objective of this study was to clarify the effect of kisspeptin-10 (kp-10) on the synthesis of progesterone (P4) in bovine granulosa cells (BGCs) and its mechanisms via microRNA 1246 (miR-1246). According to the results, we found that treating with kp-10 for 24 h could increase P4 level, the mRNA expression of the steroidogenesis-related gene steroidogenic acute regulatory protein (StAR), free cholesterol content, and decrease miR-1246 expression in BGCs. Overexpression of miR-1246 significantly inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…A kisspeptin-induced increase in P4 secretion and expression of STAR, CYP11A1 and HSD3B1 has also been reported in cultured chicken GC ( Xiao et al 2011 ). More recently, kisspeptin-10 was shown to increase P4 production and STAR mRNA expression by bovine GCs cultured in medium supplemented with 10% FCS ( Guo et al 2022 ). As such, these observations are indicative of a positive role for kisspeptin in promoting P4 synthesis, although possible effects on other ovarian steroids were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A kisspeptin-induced increase in P4 secretion and expression of STAR, CYP11A1 and HSD3B1 has also been reported in cultured chicken GC ( Xiao et al 2011 ). More recently, kisspeptin-10 was shown to increase P4 production and STAR mRNA expression by bovine GCs cultured in medium supplemented with 10% FCS ( Guo et al 2022 ). As such, these observations are indicative of a positive role for kisspeptin in promoting P4 synthesis, although possible effects on other ovarian steroids were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to steroidogenesis, it was reported that progesterone (P4) production by rat luteal cells was stimulated by kisspeptin ( Peng et al 2013 ), while hCG-induced P4 production by rat GC was attenuated by a kisspeptin antagonist, kisspeptin 234 ( Laoharatchatathanin et al 2015 ). Kisspeptin was also shown to increase P4 production by porcine GC ( Basini et al 2018 ) and bovine GC ( Guo et al 2022 ). The above reports suggest a potential role of locally produced kisspeptins in the control of ovarian function.…”
Section: Introductionmentioning
confidence: 99%
“…Kisspeptin can regulate animal reproduction by regulating follicular development through the paracrine or autocrine pathway in the gonads. Kisspeptin treatment promotes progesterone secretion in cultured bovine granulosa cells [ 24 ], while transfection of the kiss1 gene into porcine ovarian granulosa cells promotes steroid secretion [ 25 ]. Our research group also showed that kisspeptin could promote the secretion of steroid hormones and cell proliferation in ovarian granulosa cells of Tan sheep in vitro (unpublished data), but the specific molecular mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that kisspeptin-10 could significantly change the expression of circulating miRNAs (let-7e, miR-100-5p, and others) obtained from the plasma of gonads of Senegalese Sole, affecting their reproduction [ 26 ]. Kisspeptin-10 has been reported to induce progesterone synthesis in bovine granulosa cells by regulating the expression of miR-146-targeted StAR genes [ 24 ]. Therefore, we speculate that kisspeptin affects ovarian granulosa cell function by modulating miRNA and mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that functional miRNAs play an important role in regulating ovarian function, follicular development and atresia, cell proliferation and apoptosis, steroid hormone synthesis and even ovarian cancer [ 26 , 27 , 28 , 29 ]. In mammals, miR-383, miR-323-3p, miR-320a, miR-130a-3p, miR-1246, miR-31 and miR-20b influence steroid hormone synthesis in granulosa cells [ 30 , 31 , 32 , 33 , 34 , 35 ], and miR-214-3p, miR-324-3p and miR-335-5p promote granulosa cell proliferation in the ovary [ 36 , 37 , 38 ]. Unfortunately, in poultry, the study of functional miRNAs in ovarian development and function of laying hens still lags behind.…”
Section: Introductionmentioning
confidence: 99%